A predictive tool to evaluate disk brake squeal using a fully coupled thermo-mechanical finite element model - Hassan, Muhammad Zahir; Brooks, Peter C.; Barton, David C. (Inderscience Enterprises Ltd, 2009)
This paper presents a new integrated approach to the analysis of brake squeal modelling. It focuses on developing a validated thermo-mechanical finite element model by taking full account of the effect of thermal loading on the structural response of the brake. An integrated study involving time-dependent non-linear contact and a fully coupled transient thermal analysis are carried out to provide the contact and temperature distribution within the brake before executing an instability study using the complex eigenvalue technique. The results, in turn, demonstrate the fugitive nature of brake squeal through the system eigenvalues that are extracted throughout the braking period.